Automated database-guided expert-supervised orientation for immunophenotypic diagnosis and classification of acute leukemia - Lhermitte, L; Mejstrikova, E; van der Sluijs-Gelling, A J; Grigore, G E; Sedek, L; Bras, A E; Gaipa, G; Sobral da Costa, E; Novakova, M; Sonneveld, E; Buracchi, C; de Sá Bacelar, T; et al. (Leukemia, 2018)
Precise classification of acute leukemia (AL) is crucial for adequate treatment. EuroFlow has previously designed an AL orientation tube (ALOT) to guide towards the relevant classification panel (T-cell acute lymphoblastic leukemia (T-ALL), B-cell precursor (BCP)-ALL and/or acute myeloid leukemia (AML)) and final diagnosis. Now we built a reference database with 656 typical AL samples (145 T-ALL, 377 BCP-ALL, 134 AML), processed and analyzed via standardized protocols. Using principal component analysis (PCA)-based plots and automated classification algorithms for direct comparison of single-cells from individual patients against the database, another 783 cases were subsequently evaluated. Depending on the database-guided results, patients were categorized as: (i) typical T, B or Myeloid without or; (ii) with a transitional component to another lineage; (iii) atypical; or (iv) mixed-lineage. Using this automated algorithm, in 781/783 cases (99.7%) the right panel was selected, and data comparable to the final WHO-diagnosis was already provided in >93% of cases (85% T-ALL, 97% BCP-ALL, 95% AML and 87% mixed-phenotype AL patients), even without data on the full-characterization panels. Our results show that database-guided analysis facilitates standardized interpretation of ALOT results and allows accurate selection of the relevant classification panels, hence providing a solid basis for designing future WHO AL classifications.
Keywords: Young Adult; Male; Child, Preschool; mladý dospělý; Adolescent; Infant; Child; dítě; Adult; akutní myeloidní leukemie; Aged; dospělí; mužské pohlaví; senioři; akutní lymfatická leukemie; mladiství; novorozenec; předškolní dítě; akutní nemoc; Acute Disease; senioři nad 80 let; lidé; ženské pohlaví; Immunophenotyping; Humans; Infant, Newborn; kojenec; Aged, 80 and over; Female; Precursor Cell Lymphoblastic Leukemia-Lymphoma; lidé středního věku; Leukemia, Myeloid, Acute; imunofenotypizace; Middle Aged